The Relationship between Manager's Strategic Intelligence and Organization Development in Governmental Agencies in Iran (Case Study: Office of Cooperatives Labor and Social Welfare) - Baei, Fahime; Ahmadi, Masoud; Malafeh, Neda Sharifi Asadi; Baee, Abbasali (International Review of Management and Marketing, 2017)
The main purpose of this paper is to investigate the relation of managers' strategic intelligence with organization development (OD) and the relationship between the dimensions of strategic intelligence and OD in governmental agencies in Iran in 2015 (case study: Office of Cooperatives Labor and Social Welfare in Sari). “Research methodology” in this study was descriptive and correlational. To fulfill the purpose of this study, 493 staff were selected from among a total number of 920 population based on random sampling. “The data collection tools” consisted of two standard questionnaires, including strategic intelligence questionnaire (0.84 validity) and OD (0.83 validity). “The data analysis method” was inferential statistics conducting by SPSS22 software (including Durbin–Watson, multiple regression and analysis of variance test). “The results” showed that there is a positive significant relationship between manager's strategic intelligence with OD and there is a significant relationship between some dimensions of strategic intelligence such as knowledge and wisdom and practical intelligence with OD but there is no significant relationship between emotional intelligence and creativity and innovation with OD. Also the results show there is a significant difference between the dimensions mean of strategic intelligence and dimensions mean of ODs. Keywords: Interpretations of Intelligence, Strategic Intelligence, Organization Development JEL Classifications: E37, E32, C53, C5